Clinico-hematological and oxidative stress status in Nili Ravi buffaloes infected with Trypanosoma evansi. (October 2018) - Hussain, Riaz; Khan, Ahrar; Jahanzaib; Qayyum, Abdul; Abbas, Tariq; Ahmad, Maqbool; Mohiuddin, Mudassar; Mehmood, Khalid
Abstract: Hemoparasitic diseases like trypanosomiasis have an adverse influence on the health and working capability of infected animals. Monitoring and identification of blood born parasitic infections in dairy animals are of vital importance to get the optimum production. In this study blood samples were collected from Nili Ravi buffaloes (n = 390) kept at different villages of district Lodhran, Punjab province of Pakistan. Blood samples were evaluated for red blood cell counts, total and differential leukocyte counts, hematocrit, hemoglobin, total proteins and different serum parameters such as alanine aminotransferase, aspartate aminotransferase, malondialdehyde, alkaline phosphatase, lactate dehydrogenase, phosphorous, copper, calcium and magnesium. Overall prevalence of Trypanosoma evansi was 4.61% based on microscopic smear examination, 11.02% with Formol Gel Test and 16.15% with PCR. Infected buffaloes showed different clinical signs, including high fever (105 ± 1.0 °F), edema of face and legs, hyperemic mucosa of eyes, lachrymation, bulging eyes, pale mucus membranes and frequent urination. Microscopic examination of blood films showed morphologically different parasites. Statistical analysis did not indicate an association of infection based on age and sex of buffaloes. Results revealed significantly ( p  < 0.05) lower values of red blood cell counts, hemoglobin, hematocrit, mean corpuscular hemoglobin concentration and total proteins, while increased values of mean corpuscular volume, total white blood cells, monocyte, neutrophils, basophils and eosinophils in infected animals. Infected buffaloes were suffering from macrocytic hypochromic anemia. A significant ( p  < 0.05) increase in serum lipid per oxidation product (malondialdehyde) level and serum enzymes while a decrease in macrominerals and trace mineral (copper) in trypanosomiasis positive buffaloes were recorded. It was concluded that Trypanosoma evansi is prevalent in Pakistan under tropical and subtropical climatic conditions. It causes clinical disease with macrocytic hypochromic anemia and oxidative stress in infected buffaloes. Highlights: Hemoparasitic diseases like trypanosomiasis have adverse influence on health and working capability of infected animals. Monitoring and identification of blood born parasitic infections in dairy animals are important to get optimum production. Trypanosoma evansi is prevalent in Pakistan under tropical and subtropical climatic conditions. Trypanosomiasis causes clinical disease with macrocytic hypochromic anemia and oxidative stress in infected buffaloes.